1993
DOI: 10.1128/aem.59.2.485-490.1993
|View full text |Cite
|
Sign up to set email alerts
|

Methane Consumption in Temperate and Subarctic Forest Soils: Rates, Vertical Zonation, and Responses to Water and Nitrogen

Abstract: Rates of methane consumption were measured in subarctic coniferous and temperate mixed-hardwood forest soils, using static chambers and intact soil cores. Rates at both sites were generally between 1 and 3 mg of CH4 m-2 day-' and decreased with increasing soil water contents above 20%o. Addition of ammonium (1 ,umol g of soil-') strongly inhibited methane oxidation in the subarctic soils; a lesser inhibition was observed for temperate forest samples. The response to nitrogen additions occurred within a few hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
152
3
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(179 citation statements)
references
References 30 publications
(30 reference statements)
23
152
3
1
Order By: Relevance
“…Hence, we propose that the inverse relationship between nitrification and CH 4 consumption in the fertilized soils in the Harvard Forest results from NH þ 4 stimulation of nitrifier growth, combined with simultaneous but independent NH þ 4 inhibition of methanotroph activity, and that CH 4 consumption is dominated by a diminished, high-affinity methanotroph population, rather than an enlarged, low-affinity nitrifier population. This interpretation is consistent with some studies that have used non-physiological approaches [38,48] and therefore have not observed possible shifts in methanotroph enzyme function.…”
Section: Physiological Effects Of Long-term N Fertilizationsupporting
confidence: 92%
“…Hence, we propose that the inverse relationship between nitrification and CH 4 consumption in the fertilized soils in the Harvard Forest results from NH þ 4 stimulation of nitrifier growth, combined with simultaneous but independent NH þ 4 inhibition of methanotroph activity, and that CH 4 consumption is dominated by a diminished, high-affinity methanotroph population, rather than an enlarged, low-affinity nitrifier population. This interpretation is consistent with some studies that have used non-physiological approaches [38,48] and therefore have not observed possible shifts in methanotroph enzyme function.…”
Section: Physiological Effects Of Long-term N Fertilizationsupporting
confidence: 92%
“…Because the availability of atmospheric CH 4 is largest in the O horizon one would expect maximum consumption in this horizon. However, the maximum consumption is generally located in the top mineral soil (Adamsen & King, 1993;Borken et al, 2003). Methanotrophs with great affinity for atmospheric CH 4 are considered to grow very slowly (Prieme et al, 1996), and thus, methanotrophic populations could survive in the mineral soil as an ecological niche where predators are much less active compared with the O horizon.…”
Section: Effect Of Forest Type Season and O Horizon Removal On Ch 4 mentioning
confidence: 99%
“…The consumption rates of both gases by surface soils beneath forest and orchard decreased with increasing soil depth. A more rapid consumption of CH 4 and C 2 H 4 is likely to be found in forest soil rather than in orchard soil (Table 4), because the implanted orchard has been supplied continuously with N fertilizers for more than 15 years (Steudler et al, 1989;Adamsen & King, 1993;Rigler & Zechmeister-Boltenstern, 1999;Xu & Inubushi, 2004). The C 2 H 4 consumption rates of the orchard soils were more than twice as large as CH 4 consumption at a same initial concentration, whereas in forest soils, the consumption rates of both gaseous hydrocarbons were almost the same (Table 3).…”
Section: Effect Of Oxic and Anoxic Conditions On Ethylene Accumulatiomentioning
confidence: 99%